The foundation of Sociološki pregled/ Sociological Review in 1938 - Antonić, Slobodan Č. (Sociološki pregled, 2018)
The apperance of the scientific journal Sociological Review/Социолошки преглед in 1938. is an important moment for Serbian sociology. It is the developmental peak of this scientific discipline in Serbia between the two world wars. At that time, translations of significant sociological works were printed, the Institute for Sociology was founded at the Faculty of Law in Belgrade, the teaching of sociology started, and the Society for Sociology and Social Sciences (1935) was founded – publisher of the first issue of Sociological Review/Социолошки преглед (1938). President of The Society and the main editor of Sociological Review/Социолошки преглед, Djordje Tasić, has prepared the second issue for printing, but the WWII cut the further development of sociology in Serbia. Only ten years after the war began the restoration of sociological institutions and the further development of this scientific discipline in our country.Keywords: Development of Sociology in Serbia, Sociological Society, Đorđe Tasić, Faculty of Law in Belgrade.